2018
DOI: 10.2351/1.5040613
|View full text |Cite
|
Sign up to set email alerts
|

Efficient air flow control for remote laser beam welding

Abstract: Efficient air flow control plays a crucial role for the reliability of remote laser beam welding applications.Local air flows are helpful to suppress unfavorable interactions between laser radiation and welding fumes as a result of absorption and/or scattering effects. On the other hand, local and additional global flows have to be applied for emission control to protect optical components and workpieces from contamination and to avoid harmful air pollution of the atmosphere. However, the appropriate design of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Especially when processing with a CO 2 laser, where plasma forming is expected, an application of shielding gas can significantly improve the energy input by blowing the plasma away from the laser beam circumference. When processing with a fiber laser, Mahrle et al [20] found that a gas flow of 2 m/s applied by a shielding gas nozzle from a rectangular position to the straight upwards directed vapor plume is sufficient to suppress interactions between the laser beam and the plume. It seems that a reduction of the particle density in the plume reduces the energy absorption and/or scattering by the plume.…”
Section: Introductionmentioning
confidence: 99%
“…Especially when processing with a CO 2 laser, where plasma forming is expected, an application of shielding gas can significantly improve the energy input by blowing the plasma away from the laser beam circumference. When processing with a fiber laser, Mahrle et al [20] found that a gas flow of 2 m/s applied by a shielding gas nozzle from a rectangular position to the straight upwards directed vapor plume is sufficient to suppress interactions between the laser beam and the plume. It seems that a reduction of the particle density in the plume reduces the energy absorption and/or scattering by the plume.…”
Section: Introductionmentioning
confidence: 99%